Phytochemical Analysis and Determination of MIC and MFC of Cacao Leaves Extract (Theobroma cacao L.) against Malassezia furfur - Lestari, Siti Marwah; Camelia, Leonyta; Rizki, Widya Twini; Pratama, Septa; Khutami, Chindiana; Amelia, Amraini; Rahmadevi, Rahmadevi; Andriani, Yuni (Jurnal Jamu Indonesia, 2024)
Pityriasis versicolor is a disease caused by Malassezia furfur. One of the plants that can potentially act as antifungal is cacao leaves (Theobroma cacao L.), which contain several secondary metabolite compounds, including alkaloids, flavonoids, tannins, quinones, terpenoids, and saponins. This study aims to determine the phytochemical analysis and the Minimum Inhibitory Concentration (MIC) and Minimum Fungicidal Concentration (MFC) of cacao leaves ethanolic extract against M. furfur. Extracts were obtained by maceration using 70% ethanol and phytochemicals analysis using Herborne’s method. Furthermore, the extracts were made into concentrations’ variations of 3.125%; 6.25%; 12.5%; 25%; 50%; and 100% for testing antifungal activity, with 10% DMSO as negative control and 2% Ketoconazole and Itraconazole as positive controls. MIC was performed with liquid macrodilution method, and MFC was performed with spread method. The results of phytochemical analysis showed that the extract contained alkaloids, flavonoids, phenols, tannins, quinones, terpenoids and saponins. MIC value was obtained at concentration of 50% and MFC value was obtained at 100%. Cacao leaves ethanolic extract with concentration of 50% can inhibit M. furfur’s growth and with 100% can eliminate M. furfur.